2014
DOI: 10.1007/s00404-014-3176-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical and perinatal outcomes in early- and late-onset preeclampsia

Abstract: EO-PE, especially with abnormal UtA Doppler findings defines a placentation abnormality with higher perinatal adverse outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
54
5
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 19 publications
14
54
5
9
Order By: Relevance
“…It has been suggested that the pathogenesis of early‐onset preeclampsia differs from that of late‐onset preeclampsia; therefore, we examined preeclampsia subdivided into early‐onset (<34 weeks of gestation) and late‐onset (34 weeks of gestation or more) preeclampsia.…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that the pathogenesis of early‐onset preeclampsia differs from that of late‐onset preeclampsia; therefore, we examined preeclampsia subdivided into early‐onset (<34 weeks of gestation) and late‐onset (34 weeks of gestation or more) preeclampsia.…”
Section: Methodsmentioning
confidence: 99%
“…Early‐onset preeclampsia confers a high risk of life‐threatening maternal complications and often has severe maternal/fetal consequences, and early delivery is the only treatment. Late‐onset preeclampsia often has a mild clinical presentation, resulting mainly in maternal consequences …”
Section: Introductionmentioning
confidence: 99%
“…Light GHp can be asymptomatic or mild dizziness, slightly elevated blood pressure, accompanied by edema or mild proteinuria, severe GHp may cause important organs injury, occur PE or eclampsia. PE and eclampsia are the main cause of adverse maternal and perinatal outcomes, such as intrauterine growth restriction and preterm birth [19,20]. The study by Schokker SA et al [21] showed previous hypertensive disorders of pregnancy was an independent risk factor for later vascular morbidity.…”
Section: Discussionmentioning
confidence: 99%